2011
DOI: 10.1111/j.1365-2850.2011.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of an Internet‐based patient education programme in psychiatric hospitals

Abstract: Internet-based patient support systems are widely assumed to predict a future trend in patient education. Coherent information is still lacking on how patient education is adopted in psychiatric hospitals and how information technology is used in it. Our aim was to describe nurses' adoption of an Internet-based patient education programme and the variables explaining it. The study was based on Rogers' model of the diffusion of innovation. The Internet-based patient education sessions were carried out by nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…They often focused on what people were going to do soon, a decision they are about to make, or a behavior they need to alter. The diffusion of innovations theory provides an exception, as this theory considers time to be an essential factor influencing adoption [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…They often focused on what people were going to do soon, a decision they are about to make, or a behavior they need to alter. The diffusion of innovations theory provides an exception, as this theory considers time to be an essential factor influencing adoption [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Professionals should also support the use of digital health interventions; their attitudes are crucial for successful implementation of health technology in patient daily care [ 88 ]. Our previous studies have shown that staff members may still be less willing to adopt new technology-based interventions into mental health care [ 89 , 90 ] as they tend to prefer traditional face-to-face methods in mental health care services [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…internet-based patient education programme) and the authors of a given publication (e.g. Anttila et al, 2011). In addition we included whether the innovation diffused in a business-to-business or business-to-consumer setting.…”
Section: Methodsmentioning
confidence: 99%